(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aims to analyze the dramaturgical text The mother, by Bertolt Brecht, dated 1931, using as a reference the concept of change of function developed by the author himself. Based on a preliminary analysis of the text and its dialogue with historical materialism, categories such as narrativity, education, and dialectics were identified. These categories allowed for an understanding of the strategies employed by Brecht to subvert the function of theatrical elements and present them to the audience in a way that made the theatrical experience useful to the political struggle of the working class.